Eskimo Art in a Community College Library - Rink, Bernard C. (Association of College and Research Libraries. American Library Association, 1964)
Made available in DSpace on 2013-01-29T18:26:33Z (GMT). No. of bitstreams: 2 license.txt: 4922 bytes, checksum: 910b249b4beec47e7ab768910c8f966f (MD5) crl_25_02_113_opt.pdf: 558589 bytes, checksum: 99a53e70ba5702f9b8e9528b77df2124 (MD5) Previous issue date: 1964-03 published or submitted for publication